Putusan Mahkamah Agung Perlindungan Konsumen, Pasca Undang-Undang No. 21 Tahun 2011 Tentang Otoritas Jasa Keuangan - Rachmanto, A Dwi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 2 (2020)DO - 10.24843/JMHU.2020.v09.i02.p12, 2020)
The majority of civil case decisions specifically consumer protection are closely correlated with the financial services sector. Looking at and studying the verdicts of consumer protection cases contained in the Supreme Court (MA) website, it can be concluded that the consumer protection cases have increased significantly in the last 3 (three) years, between 2013 and 2017, especially after the enactment of Act Number 21 the Year 2011 concerning Financial Fervices Authority. This paper will analyze non-financial service case decisions, at least from the point of view of whether non-financial service case decisions are appropriately handled and understood by Supreme Court judges, BPSK Members, and by disputing parties based on Act Number 9 of 1999 Concerning Consumer Protection. The purpose of writing is to know what has been exactly done by BPSK and the judge and to analyze what is not appropriate normatively. The decision analysis is based on the classification of consumers, business actors, and the authority of the Consumer Dispute Settlement Agency (BPSK). This paper will analyze 14 non-financial services Supreme Court (MA) decisions in the span of time between 2013 and 2017, and use the normative juridical research method. From the results of the verdict research, it appears that the understanding of MA judges, BPSK members, and the parties to the dispute has not fully understood the understanding of consumers, business actors, and the authority of BPSK in handling cases. Mayoritas putusan perkara perdata khusus perlindungan konsumen berkorelasi erat dengan bidang jasa keuangan. Melihat dan mempelajari putusan perkara perlindungan konsumen yang terdapat dalam laman Mahkamah Agung (MA) dapat disimpulkan bahwa perkara perlindungan konsumen mengalami peningkatan signifikan dalam kurun 3 (tiga) tahun terakhir, antara tahun 2013 sampai dengan tahun 2017,  khususnya setelah berlakunya UU Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan. Tulisan ini akan menganalisis putusan perkara non jasa keuangan, setidaknya dari sudut pandang apakah putusan perkara non jasa keuangan telah tepat ditangani dan dipahami oleh hakim MA, Anggota BPSK dan  oleh para pihak yang bersengketa berdasarkan UU Nomor 9 Tahun 1999 Tentang Perlindungan Konsumen. Tujuan penulisan mengetahui apa yang telah tepat dilakukan oleh BPSK dan hakim serta menganalisis apa saja yang tidak tepat secara normatif. Analisis putusan dilakukan berdasarkan klasifikasi konsumen, pelaku usaha, dan kewenangan Badan Penyelesaian Sengketa Konsumen (BPSK). Tulisan ini akan menganalisis 14 putusan MA (MA) non jasa keuangan dalam rentang waktu antara tahun 2013 sampai dengan tahun 2017, dan menggunakan metode penelitian yuridis normatif. Dari hasil penelitian putusan nampak bahwa pemahaman hakim MA, Anggota BPSK dan para pihak yang bersengketa belum sepenuhnya memahami pengertian konsumen, pelaku usaha, dan kewenangan BPSK dalam menangani perkara.